2008
DOI: 10.1345/aph.1l031
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Worsening and Exacerbation After Venlafaxine and Duloxetine Therapy

Abstract: Use of drugs that increase serum norepinephrine levels, such as the SNRIs, may be potentially deleterious in individuals with unstable or advanced HF. These medications should be avoided or used with caution and monitored regularly in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…[44][45][46][47] Most of the research examining cardiac effects of venlafaxine has been conducted in elderly patients and has suggested that venlafaxine can contribute to acute myocardial infarction, increased heart rate, and heart failure. [48][49][50] Given the demonstrated increased risk of postpartum hemorrhage associated with hypertensive disorders, 14,51 and the higher rate of hypertension in the women in our cohort using venlafaxine compared with SSRIs (12.8% compared with 7.0%), it is plausible that venlafaxine may increase the risk of postpartum hemorrhage through similar noradrenergic effects. However, we would expect hypertension to be on the causal pathway between venlafaxine use and postpartum hemorrhage, which was not borne out in our results.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] Most of the research examining cardiac effects of venlafaxine has been conducted in elderly patients and has suggested that venlafaxine can contribute to acute myocardial infarction, increased heart rate, and heart failure. [48][49][50] Given the demonstrated increased risk of postpartum hemorrhage associated with hypertensive disorders, 14,51 and the higher rate of hypertension in the women in our cohort using venlafaxine compared with SSRIs (12.8% compared with 7.0%), it is plausible that venlafaxine may increase the risk of postpartum hemorrhage through similar noradrenergic effects. However, we would expect hypertension to be on the causal pathway between venlafaxine use and postpartum hemorrhage, which was not borne out in our results.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports in the literature of myocardial infarction [23], tachycardia [24], worsening heart failure [25] and cardiovascular-related death [26], whilst receiving venlafaxine or duloxetine, and particular warnings have been appended to product information. It may be appropriate to re-examine the nature of the cardiac event profile associated with these agents in order to facilitate both appropriate diagnosis and treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual clinical effect in individual patients, especially those with comorbid hypertension or heart disease, cannot be predicted based on aggregate data and baseline and periodic monitoring of blood pressure and heart rate is recommended. 37 Also, concerns that increased circulating norepinephrine levels induced by duloxetine could negatively affect cardiac function and induce harmful cardiac remodeling have been voiced, 52 implying that duloxetine treatment may negatively impact patients with pre-existing congestive heart failure (CHF). This concern is supported by case reports of worsening heart failure after initiating treatment with venlafaxine 53 and duloxetine.…”
Section: Dovepressmentioning
confidence: 99%
“…This concern is supported by case reports of worsening heart failure after initiating treatment with venlafaxine 53 and duloxetine. 52 No prospective studies have evaluated the effect of duloxetine treatment in patients with CHF.…”
Section: Dovepressmentioning
confidence: 99%